Parents at work: men and women participating in the labour force - Rand Corporation, Santa Monica; Miani, Celine; Hoorens, Stijn (Santa Monica, 2014)
"This statistical paper focuses on the relationship between parenthood and employment. The report looks into a number of related aspects and gender differences are then investigated by examining these various aspects and contrasting men and women. The analysis of these aspects focused on employment rate differences between parents and nonparents; working hours among parents and non-parents; gender inequalities with regard to work interruption and parental leave; and attitudes towards parental involvement in work and care."